The application of GHz band charge pump rectifier and rectenna array for satellite internal wireless system. Issue 2 (28th September 2019) - Wang, Ce; Yang, Bo; Kojima, Seishiro; Shinohara, Naoki
Abstract: An internal wireless system (IWS) for satellites was proposed in a previous study to reduce the weight of satellites. It is a system that uses wireless communication modules to communicate between the satellite's subsystems. We proposed a complete IWS that employs microwave wireless power transmission technology, and we proposed a design of GHz band high efficiency rectifier based charge pump rectifiers with a class-f filter called class-f charge pump rectifiers. We theoretically compare the diode losses in a charge pump and single shunt rectifier, and experimentally verify the results. Apart from this, we consider that the class-f charge pump rectifiers will be used for a rectenna array. In order to know the direct current (DC) load change of class-f charge pump circuits is connected as a rectenna array, we measured the conversion efficiencies of a 2 by 2 rectenna array, connected in series and in parallel. The results of the experiment indicate that the optimum load of the rectifier changes to four times DC load when connected in series, and to 1/4 the DC load when connected in parallel.